Secondary Syphilis with Multiple Co-Infections of Human Immunodeficiency Virus (HIV), Tuberculosis (TB), and Oral Candidiasis in a 19-Year-Old Men Who Have Sex with Men (MSM): A Case Report - Melin, Uliana Nur; Adhi Dharmasanti, Prasti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Syphilis is an infection of the Treponema pallidum bacteria that often occurs along with conditions such as Human Immunodeficiency Virus (HIV) infection, tuberculosis (TB), and oral candidiasis. A weakened immune system affects the complex interactions between these conditions and the clinical presentation as well as the therapeutic management provided to patients. Case: A 19-year-old male with a history of HIV complained of lesions on the skin and mouth. Anamnesis, physical examination, and serological test results establish the diagnosis of secondary syphilis and pulmonary tuberculosis, characterized by a one-month history of phlegm coughing and weight loss, was confirmed via sputum testing. Additionally, oral candidiasis was identified based on clinical examination. Discussion: The patient exhibited complex complications from secondary syphilis, HIV infection, TB, and oral candidiasis. In cases of syphilis with HIV, the appropriate treatment is three doses of Benzathine Penicillin G. Anti-Tuberculosis Drugs administration for TB was adjusted based on HIV status and therapy response, and antifungal fluconazole for oral candidiasis. Conclusions: This case highlights the importance of proper management and close monitoring of patients with multiple infectious conditions, including treatment of syphilis patients that has  a higher incidence in men who have MSM, HIV, TB, and oral candidiasis. Timely and appropriate therapy strategies are essential to minimize complications and improve clinical outcomes.